Preparedness revisited: civilian societies and the campaign for american defense, 1914-1920 - Franz, Manuel (The journal of the gilded age and progressive era, 2018)
Civilian societies advocating a bold defense program were arguably the most visible manifestation of the American preparedness campaign in World War I. Though historians have acknowledged the significance of the broader preparedness movement in a number of studies, they have often marginalized its civilian branch in general and defense societies in particular. This article examines the structures, activities, and objectives of two major organizations active in the movement in order to challenge historiography's traditional view on preparedness. Exploring the key role of the National Security League and the American Defense Society between 1914 and 1920, the article presents two main arguments: First, civilian societies were not merely the appendix to a centralized campaign dominated by military professionals and politicians associated with the defense cause but acted as principal agents of preparedness. Second, the historiographic time frame of preparedness cannot be limited chronologically to America's years of neutrality but must include the period after April 1917.
Gesehen am 14.11.2018